Analisis Nilai Tukar Nelayan (NTN) dan Kebiasaan Menabung Masyarakat Nelayan di Kampung Teluk Sulaiman Kecamatan Biduk-Biduk Kabupaten Berau: The Analysis of Fishers’ Terms of Trade (FTT) Index and the Saving Habit of Fishing Communities In Teluk Sulaiman Village, Biduk-Biduk Sub-district, Berau Regency - Nedia Nedia Saputri; Erwiantono; Heru Susilo (2339-1324, 2022)
This study aims to know the level of fishers' welfare and the saving habits of fishing communities in the Teluk Sulaiman Village, Biduk-Biduk Sub-district, Berau Regency. The study was conducted in Teluk Sulaiman Village with 30 respondents based on three types of fishing gear used by fishers. The study method used was purposive sampling. In general, the analytical result of FTT showed that the average FTT value for fishing households from three types of fishing gear in 2018 and 2019 was more than one. Meanwhile, the analytical result of the average FTT index of fishing households in 2018 and 2019 was under 100%. The fishing households experienced a surplus financial condition and could save money based on the FTT analysis. The majority of fishing households did saving activities at the Bank and keeping cash at home. The dominant saving was uncertain with a percentage of 10% - 15% and 15% - 20% of income. Fishing households saving money for productive purposes as capital to develop business were 18 peoples with a percentage of 100% and they saving money for non-productive purposes as a capital social were 17 peoples with a percentage of 94.45% and family funds were 18 peoples with a percentage 100%.